2006
DOI: 10.1111/j.1365-2125.2006.02726.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gender, age, diabetes mellitus and renal and hepatic impairment on tadalafil pharmacokinetics

Abstract: AimsTo evaluate the effects of gender, age, diabetes mellitus, renal and hepatic impairment on tadalafil pharmacokinetics and tolerability. MethodsSix single-dose (5, 10 or 20 mg orally) clinical pharmacology studies were conducted in the UK, Belgium, Poland and Germany in healthy male and female subjects, elderly subjects and subjects with diabetes mellitus, renal impairment, end-stage renal failure (ESRF) or hepatic impairment. The gender study also incorporated administration of 10 mg tadalafil daily for 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
38
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 37 publications
4
38
0
Order By: Relevance
“…Tadalafil has a longer half-life than sildenafil (17.5 hours versus 4 hours), which permits single daily dosing, and, unlike sildenafil, tadalafil absorption is unaffected by food or alcohol consumption. [14,33] Tadalafil metabolism in the geriatric population and in patients with mild to moderate hepatic impairment is similar to that in the general population, [34,35] whereas the metabolism of sildenafil is altered in these subgroups. [36] Finally, the PDE5 selectivity of tadalafil is higher than that of sildenafil, which results in a better adverse effect profile.…”
Section: Discussionmentioning
confidence: 99%
“…Tadalafil has a longer half-life than sildenafil (17.5 hours versus 4 hours), which permits single daily dosing, and, unlike sildenafil, tadalafil absorption is unaffected by food or alcohol consumption. [14,33] Tadalafil metabolism in the geriatric population and in patients with mild to moderate hepatic impairment is similar to that in the general population, [34,35] whereas the metabolism of sildenafil is altered in these subgroups. [36] Finally, the PDE5 selectivity of tadalafil is higher than that of sildenafil, which results in a better adverse effect profile.…”
Section: Discussionmentioning
confidence: 99%
“…The t max value of tadalafil in hyperlipidemic rats tended to be extended as compared with that in control rats, but the difference was not significant. 23 Therefore, together with the fact that tadalafil is a drug with a low hepatic extraction ratio, 8,12 its disposition seems rather susceptible to changes in intrinsic metabolic clearance (CL int ) and/or the UBF (f u ) of the drug.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that gender, age, and hepatic impairment have no effect on the pharmacokinetics of tadalafil in adults, although systemic exposure in the elderly was 25% greater than in young subjects. 12 Although tadalafil had negligible renal clearance, total clearance of tadalafil was reduced by mild or moderate renal insufficiency, with a corresponding prolongation of t 1/2 and exposure approximately twice that in healthy subjects. 12 The mechanisms underlying the decrease of total clearance associated with renal impairment remain unclear.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…14 Similarly, the results of the use of tadalafil in an HD patient group showed that it is effective and welltolerated. 40 In our study of an HD patient group, udenafil was found to be an effective treatment for ED and other accompanying sexual function disorders. All 31 patients included in our study provided positive feedback regarding their ongoing treatment at the checkup after 1 month, which is another positive result.…”
Section: Discussionmentioning
confidence: 99%